Phytoseiid mites (Parasitiformes, Phytoseiidae) associated with cultivated and spontaneous plants in a complex agroecosystem (Bollettino di zoologia agraria e bachicoltura, 2024)
Data on the specific composition, dynamics of populations, and similarities amongphytoseiid species associated with various cultivated and spontaneous plantspresent in a complex agroecosystem, are here reported. 11 species, belonging to7 genera, have been collected. Euseius stipulatus (Athias-Henriot) was the mostfrequently found species on all the surveyed plants, followed by Euseius finlandicus(Oudemans) (91%). Typhlodromus exhilaratus Ragusa and Amblyseiusandersoni (Chant) were found on 73% of plants, while the remaining species weresporadically collected. E. stipulatus was the dominant species on vines, on spontaneousherbaceous plants and asparagus, maize and turnip tops, while E. finlan-dicus was the dominant species on nuts, tomatoes and potatoes. High values ofsimilarity were ascertained between the two cultivars of vines, spontaneous herbaceousplants present between rows and white willows (0.80-0.89) as well asbetween nuts and asparagus (0.71). The data obtained and analysed show anexchange of phytoseiid species among the different plant species present in theagroecosystem even if the permanence of the various species on various plants ismost probably linked to the preference of each species towards the habitats offeredby the various plants.
Keywords: Phytoseiidae; spontaneous-cultivated plants; similarity